Reduction of cholesterol and markers of oxidation in serum of hypercholestrolemic patients treated with lycosome formulation of simvastatin - Petyaev, Ivan M.; Dovgalevsky, Pavel Y.; Chalyk, Natalia E.; Klochkov, Victor; Kyle, Nigel H. (International Journal of Research in Medical Sciences, 2016)
Background: Use of microencapsulated HMG-CoA reductase inhibitors (statins) might be extremely helpful in the prevention of their side effects. Methods: 24 volunteers with hypercholesterolemia were given once daily 20 mg of lycosome-formulated Simvastatin fused with 7 mg lycopene (Lyco-Simvastatin) or the same amount of unmodified Simvastatin with no lycopene. Control patients received 7 mg of lycopene alone. Plasma lipids and oxidative markers were measured after 4 weeks of treatment. Results: Both formulations of Simvastatin, but not lycopene, caused a reduction in serum total cholesterol and LDL at the intermediate (end of 2nd week) and final (end of 4th week) points of interventional period. Notably, reduction of total cholesterol and LDL in the 4th week of the trial was more profound in patients treated with Lyco-Simvastatin versus unmodified Simvastatin (P<0.05). Patients treated with Lyco-Simvastatin showed a reduction in serum Apo B level, which was not observed in other groups. Lycopene treatment caused a modest but statistically significant decrease in serum triglyceride. However, the triglyceride-lowering effect of Simvastatin was more profound in the case of Lyco-Simvastatin treatment. Lycopene as well as unmodified Simvastatin gave a marginal reduction of Inflammatory Oxidative Damage. Remarkably, the combined formulation of Simvastatin and lycopene gave a significant reduction in the values for oxidative damage (reduction of median by 112.5 µM, P<0.05). Similar synergistic effect was observed when levels of oxidized LDL were analyzed. Conclusions: Lycosome-formulated microencapsulated Simvastatin has a better cholesterol-lowering and antioxidant capacity presumably due to enhanced bioavailability of the drug and synergism with lycopene.